The effect of renewable energy use and economic growth on pollution in the EUROZONE - Fotis, Panagiotis Nikolaos; Pekka, Victoria (Economics and Business Letters, 2017)
The aim of this paper is to empirically examine the effect of renewable energy use and economic growth on pollution within EUROZONE from 2005 to 2013 by utilizing Dynamic Panel Generalized Method of Moments approaches. The empirical results reveal that economic growth positively affects environmental pollutants. The use of renewable sources of energy negatively affects pollution. The more the renewable energy we use the less the air pollution. However, energy saving and energy intensity contribute to more air pollution.